PERANCANGAN MEDIA VISUAL BLIND BOX SEBAGAI REPRESENTASI AKULTURASI BUDAYA TIONGHOA-NUSANTARA: Designing a Blind Box Visual Medium as the Acculturation of Chinese–Nusantara Culture Representation - Naomi; Andreana Lingga Sekarasri (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2025)
Designing a Blind Box Visual Medium as the Acculturation of Chinese–Nusantara Culture Representation. This study aims to design a blind box as a medium to introduce and preserve the acculturation of Chinese–Nusantara culture among young generations. It is essential for young people to recognize products of cultural acculturation in order to understand cultural diversity and the historical heritage that shapes national identity. The blind box was chosen as the medium because its element of surprise can stimulate curiosity and interest among youth toward cultural richness. This research employed a qualitative approach, with data collected through observation, interviews, and literature study. The focus was directed toward representing cultural elements through character designs, such as traditional clothing, cuisine, architecture, music, folk games, decorative arts, and traditional transportation. The result of this study is a prototype blind box featuring a cultural character named Amoi, which visually represents Chinese–Nusantara acculturation. The findings conclude that the blind box can serve as an effective medium to spark curiosity among youth about cultural values, although it remains limited to specific themes. Therefore, further research is expected to develop the concept more broadly.